Movekids Flashcard Learning Media to Enhance Physical Literacy for Third Grade Elementary School Students - Asep Sujana; Selvi Atesya Kesumawati; Aprizal Fikri; Selvi Melianty; Arif Hidayat (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to develop the Movekids Flashcard as a learning medium to enhance physical literacy among third-grade elementary school students. The research follows the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The study involved 18 third-grade students from SD Negeri Talang Giring in the small-scale trial phase and 46 students from SD Negeri Bunga Sekoti and SD Negeri Kotanegara in the large-scale trial phase. Expert judgment in this study consisted of three experts: one learning media expert, one motor learning expert, and one physical educator. The content validity of the learning media was assessed using the Content Validity Index (CVI) and Content Validity Ratio (CVR), yielding a CVI score of 3.83 and a CVR score of 0.25. These results indicate a high level of content validity, allowing the study to proceed to the field trial phase. The findings suggest that the Movekids Flashcard effectively enhances students' physical literacy and can serve as an innovative learning medium in elementary school physical education.